Development of interactive learning media based on silayar folklore to improve reading comprehension of elementary school students - Batubara, Fikri Husin; Hasibuan, Elpina Yanti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
The purpose of this study was to determine the Development of Interactive Learning Media Based on Silayar Folklore to Improve Reading Comprehension of Elementary School Students The development model used in this study is the 4D development model consisting of the main stages, namely: (1) Define, (2) Design, (3) Develop, (4) Disseminate. The results showed that the learning media based on Silayar folklore developed was valid and effective in improving the reading comprehension skills of fifth grade students of SD Negeri 1 Kutacene. Product validity was proven to be high through expert assessment. Product trials indicated significant improvement in students' reading comprehension skills, with 89% of children showing improvement. The Silayar folklore-based learning media made it easy to practice learners' reading comprehension skills, accompanied by learners' excitement and enthusiasm. Implementation in schools is recommended with the support of the school principal, and teachers can adopt this media as an interesting alternative in training students' reading comprehension skills. This conclusion encourages further research with the development of more interesting learning media. Overall, the use of folklore-based learning media makes a positive contribution in improving the reading comprehension skills of grade V elementary school students. Suggestions for future research can develop other story-based learning media, not only folklore-based but also Islamic story-based, etc. Future researchers can focus on developing more innovative and interesting learning media variants.